Postmethod Pedagogy and Iranian EFL Teachers’ Understandings: Is a Promising Trend on the Way? - Nasser Rashidi (Issues in Language Teaching, 2017)
The profession of second language teaching has experienced fundamental fluctuations in both theory and practice. With its own proponents and opponents, the postmethod was considered as the practical and reasonable solution to the limitations of the confining concept of the method. The purpose of this qualitative study was to elicit nonnative EFL teachers’ viewpoints and perceptions regarding postmethod pedagogy. In fact, the researchers were interested to know about nonnative EFL teachers’ perceptions of postmethod condition regarding their own context and needs. Selected based on purposive sampling procedure, the participants of this study were 10 nonnative EFL teachers categorized into three groups based on their teaching experience. The participants took part in semi-structured interviews and they were asked a series of questions to elicit their perceptions and interpretations of postmethod. The results of the study revealed some rays of hope in some cases, though not promising in a full manner. In other words, although nonnative EFL teachers could not mention the postmethod principles explicitly, they showed a logical understanding of postmethod pedagogy tenets and its applications in their teaching practices and procedures. The results of this study can help teacher educators design more effective teacher education courses and in-service programs to enhance nonnative EFL teachers’ viewpoints and perceptions regarding postmethod pedagogy and its implications in language teaching and learning processes.